Increased Death of Peripheral Blood Mononuclear Cells after TLR4 Inhibition in Sepsis Is Not via TNF/TNF Receptor-Mediated Apoptotic Pathway. (25th October 2021) - Chu, Chien-Ming; Chiu, Li-Chung; Yu, Chung-Chieh; Chuang, Li-Pang; Kao, Kuo-Chin; Li, Li-Fu; Wu, Huang-Pin
Abstract : Background . Apoptosis is one of the causes of immune depression in sepsis. Pyroptosis also occurs in sepsis. The toll-like receptor (TLR) 4 and receptor for advanced glycation end products (RAGE) have been shown to play important roles in apoptosis and pyroptosis. However, it is still unknown whether TLR4 inhibition decreases apoptosis in sepsis. Methods . Stimulated peripheral blood mononuclear cells (PBMCs) with or without lipopolysaccharides (LPS) and high-mobility group box 1 (HMGB1) were cultured with or without TLR4 inhibition using monoclonal antibodies from 20 patients with sepsis. Caspase-3, caspase-8, and caspase-9 activities were measured. The expression of B cell lymphoma 2 (Bcl2) and Bcl2-associated X (Bax) was measured. The cell death of PBMCs was detected using a flow cytofluorimeter. Results . After TLR4 inhibition, Bcl2 to Bax ratio elevated both in LPS and HMGB1-stimulated PBMCs. The activities of caspase-3, caspase-8, and caspase-9 did not change in LPS or HMGB1-stimulated PBMCs. The cell death of LPS and HMGB1-stimulated CD8 lymphocytes and monocytes increased after TLR4 inhibition. The cell death of CD4 lymphocytes was unchanged. Conclusion . The apoptosis did not decrease, while TLR4 was inhibited. After TLR4 inhibition, there was an unknown mechanism to keep cell death in stimulated PBMCs in patients with sepsis.